SISTEM IOT UNTUK MONITORING SUHU KELEMBABAN UDARA KUMBUNG JAMUR TIRAM PATEAN - Dendy Kurniawan; Ahmad Ashifuddin Aqham; Catur Wahyu Aji Siswoyo; Iman Saufik Suasana; Edy Siswanto (Informatika: Jurnal Teknik Informatika dan Multimedia, 2025)
The agricultural sector supports economic growth, with cultivation essential for food production. Oyster mushrooms (Pleurotus ostreatus) require stable temperature and humidity to thrive. In Kendal Regency, oyster mushroom farmers still rely on manual spraying, which is time-consuming and labor-intensive. To address this, a monitoring and control system was developed using a DHT22 sensor and Wemos D1 R1 microcontroller connected to IoT. This system enables real-time temperature and humidity monitoring via an Android app, allowing farmers to check conditions remotely and efficiently manage the oyster mushroom barn environment.